Successful Expression of DNA-Based Vaccine Construct Encoding Human Papillomavirus Type 16 E7 Fused to Heat Shock Protein B1 in Eukaryotic Cells - Reyhane Najafi1; Azam Bolhassani2*; Maryam Montazeri1; Elnaz Agi3 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Developing potent therapeutic vaccines against human papillomaviruses (HPVs) is crucial for the effective management of various HPV-associated cancers. DNA-based vaccines are attractive due to their safety, stability, and capacity to elicit a targeted immune response against specific antigens. Heat shock proteins (HSPs) can enhance the efficacy of DNA vaccines when used as adjuvants. In this study, we created a recombinant DNA molecule by fusing the HPV16 e7 gene with either the hspB1 or hsp27 gene and assessed its expression in a eukaryotic cell line. Methods: Initially, we constructed a recombinant eukaryotic expression vector by inserting the hsp27-e7 fusion gene into the pcDNA3.1 (-) vector. The concentration and purity of the sample were evaluated using NanoDrop spectrophotometry. We cultured human embryonic kidney 293T (HEK- 293T) cells in RPMI 1640 medium and transfected them with the pcDNA3.1-hsp27-e7 construct using Lipofectamine 2000 transfection reagent. After 48 hours, we assessed the expression of the Hsp27-E7 fusion protein by western blotting using an anti-E7 monoclonal antibody. Results: We successfully subcloned the hsp27-e7 fusion gene into the pcDNA3.1 (-) vector, and enzymatic digestion confirmed a distinct ~975 bp band on an agarose gel. The concentration and purity of the recombinant DNA vector in a 10 mL culture were measured to be 210 ng/μL and 1.86, respectively. Furthermore, the expression of the Hsp27-E7 fusion protein in HEK-293T cells was confirmed by Western blot analysis, which detected a distinct band of approximately 38 kDa. Conclusion: Our in vitro findings demonstrate successful expression of the DNA construct encoding the hsp27-e7 gene, which can be utilized as a DNA vaccine for future in vivo investigations.